2019
DOI: 10.3390/molecules24142527
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Combination Chemotherapy: The Implication and Efficacy in Cancer

Abstract: Many chemotherapeutic drugs have been used for the treatment of cancer, for instance, doxorubicin, irinotecan, 5-fluorouracil, cisplatin, and paclitaxel. However, the effectiveness of chemotherapy is limited in cancer therapy due to drug resistance, therapeutic selectivity, and undesirable side effects. The combination of therapies with natural compounds is likely to increase the effectiveness of drug treatment as well as reduce the adverse outcomes. Curcumin, a polyphenolic isolated from Curcuma longa, belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(129 citation statements)
references
References 129 publications
(135 reference statements)
2
124
1
2
Order By: Relevance
“…Curcumin administered with various drugs can be efficacious for treatment of many diseases and conditions [53]. Combination therapy reduced the signs and symptoms of diseases, and in many instances, prevented diseases.…”
Section: Health Promotion and Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin administered with various drugs can be efficacious for treatment of many diseases and conditions [53]. Combination therapy reduced the signs and symptoms of diseases, and in many instances, prevented diseases.…”
Section: Health Promotion and Therapeutic Applicationsmentioning
confidence: 99%
“…In this regard, curcumin-mediated enhanced expression of pro-apoptotic molecules such as BAK and BID, and reduced expression of anti-apoptotic molecules such as BCL-2, BCL-XL and MCL-1 in the chemotherapy-treated cancer cells remains an active area of research. Furthermore, curcumin's synergistic effect on docetaxel to activate tumor suppressor p53 and inhibit phosphoinositide 3-kinase (PI3K)/AKT, epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor type 2 (HER2) are noteworthy reports [53,55,57].…”
Section: Health Promotion and Therapeutic Applicationsmentioning
confidence: 99%
“…Here, we evaluated whether long-term exposure to low-dose curcumin affected the response of cells to the chemotherapy agents, cisplatin and pemetrexed, used as first-line chemotherapy in NSCLC of non-squamous histology with no known EGFR sensitising mutation, and also at relapse for those with EGFR mutation. Several reports have previously suggested that curcumin may offer a sensitising effect when administered at high doses in conjunction with chemotherapy drugs [12][13][14][15]. When given at low-dosage over three months (which is more consistent with administration in a preventive setting), no sensitising effect was observed in three lung cancer cell lines exhibiting different mutational spectra (A549: K-ras mutant; PC9: EGFR driver mutation; PC9ER: EGFR driver mutation but exhibiting erlotinib resistance).…”
Section: Discussionmentioning
confidence: 75%
“…This phenomenon has led to a decrease in the potential of chemotherapeutic agents such as paclitaxel, oxaliplatin, temozolomide (TMZ), and so on (Pokhriyal, Hariprasad, Kumar, & Hariprasad, 2019). Much attention has been made towards the molecular pathways that contribute to the resistance of cancer cells to chemotherapy (Tan and Norhaizan, 2019 Autophagy is a catabolic process that plays a significant role in providing energy during stress conditions such as starvation (Galluzzi & Green, 2019). This mechanism contributes to the degradation of aged or damaged organelles and components (Ashrafizadeh, Yaribeygi, Zare, Butler, Barreto, & Sahebkar, 2019).…”
Section: Antitumor Activitymentioning
confidence: 99%